THE ROLE OF COMMUNICATION IN THE LEGAL PROTECTION OF PATIENTS IN HEALTH SERVICES IN INDONESIA: A LITERATURE REVIEW - Gunawan Widjaja; Dyah Ersita Yustanti; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (Jurnal Komunikasi, 2025)
Communication plays a central role in the legal protection of patients in health services in Indonesia. Through effective communication, patients' rights such as the right to medical information, informed consent, and confidentiality of health data can be fulfilled optimally. Clear and transparent communication not only strengthens the patient's legal position, but also minimises potential disputes between patients and health workers. However, the implementation of ideal communication still faces various obstacles, such as time constraints, low health literacy, and the challenge of adapting digital technology in health services. This literature review confirms the importance of strengthening the communication capacity of health workers, educating patients, and updating regulations so that patient legal protection through communication can be realised effectively and evenly throughout Indonesia